MENINGKATKAN KEMAMPUAN GURU DALAM MENYUSUN SILABUS DAN RPP MELALUI SUPERVISI AKADEMIK DI SD N GAMBIRAN YOGYAKARTA TAHUN 2016 - Beny Susetya (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2017)
The current government policy provides the widest possible opportunity for teachers to demonstrate their competence for the embodied superior work through improved learning outcomes and positive behaviors of learners. Teachers play an important role in realizing innovative, creative, effective schools. This continuous academic supervision can improve teachers’ competence in the preparation of syllabus and lesson implementation plan in primary school Gambiran UPT Eastern TK / SD. It can be proven from the results of the same score both in the first cycle and the second cycle. Percentage mastery of teachers in the preparation of syllabus and RPP in the first cycle shows the number of 55%, and in the second cycle of 85%. Thus there is a vivid increase in mastery from the first cycle to the second cycle.